“Tri hita karana” Life ideology as a cultural identity of balinese society reflected in elizabeth gilbert’s eat pray love (Anthropological Approach In Literature) - Hadiyanto Hadiyanto (E3S Web of Conferences, 2022)
This research paper discusses the everyday life ideology of Balinese society popularly called “Tri Hita Karana” as a local cultural identity reflected in a literary work of Elizabeth Gilbert’s Eat Pray Love by using anthropological approach in literature. The result of the research indicates that Balinese society culturally applies and strongly relies on “Tri Hita Karana” life ideology to live a life on the basis of three sources of happiness. This life ideology continually becomes the typical-local-cultural identity of Balinese people since it evidently gives them happiness and prosperity. Balinese society really believes in “Tri Hita Karana” life ideology covering three concepts of balanced harmonious relationship, that is, “parahyangan”, “pawongan”, and “palemahan”. “Parahyangan” concept emphasizes on a harmonious relationship between humans and God, “pawongan” concept refers to a harmonious relationship between humans and humans, and “palemahan” concept refers to a harmonious relationship between humans and nature. In relation to “parahyangan” concept, Balinese society obediently performs some religious practices, several traditional rituals, and certain offering ceremonies. In connection with “pawongan” concept, Balinese people sincerely build up a good relationship by cooperating with others in many aspects of social life. Referring to “palemahan” concept, Balinese people maintain the nature around well, keep the environment clean, preserve the green forest, and conserve a lot of protected animals.